Can a Specific Computed Tomography-Based Assessment Predict the Ophthalmological Outcome in Pure Orbital Floor Blowout Fractures?. Issue 8 (November 2016) - Bruneau, Stéphane; De Haller, Raoul; Courvoisier, Delphine S.; Scolozzi, Paolo
Abstract : Abstract: The aim of this study was to determine the predictive value of a specific computed tomography (CT)-based assessment for the final functional ophthalmological outcome in pure orbital floor blowout fractures. Data of 34 consecutive patients with pure blowout fractures who had undergone a period of at least 6 months of medical and ophthalmological follow-up were analyzed. The following 3 CT scan-based parameters were included: area ratio of the fractured orbital floor (RF), maximum height of periorbital tissue herniation (MH), and a 4-grade muscular subscore (MSS) describing the inferior rectus muscle displacement relative to the orbital floor level. The orthoptic complications (diplopia, enophthalmos, and ocular motility restriction) were evaluated by an experienced strabologist. The CT parameters' predictive value was analyzed using receiver operating characteristic curves and area under the curve (AUC), logistic regression, and Spearman correlation. The RF had a significant predictive value for enophthalmos appearance (AUC = 0.75, P = 0.02), and MH for diplopia (AUC = 0.80, P = 0.03). Among patients with complications, the relevance of MSS and MH as well as the severity of vertical deviation were also clinically strongly associated (rho = −0.52 and −0.56). Our study revealed the significantly predictive value of RF for occurrence of enophthalmos and of MH for diplopia persistence. Although statistically unable to predict the occurrence of ocular motility restriction, MH and MSS were clinically strongly correlated with the severity of ocular deviation limitations.